2012
DOI: 10.1039/c2cp22873d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible formation of a PdCx phase in Pd nanoparticles upon CO and O2 exposure

Abstract: The structure and chemical composition of Pd nanoparticles exposed to pure CO and mixtures of CO and O(2) at elevated temperatures have been studied in situ by a combination of X-ray Diffraction and X-ray Photoelectron Spectroscopy in pressures ranging from ultra high vacuum to 10 mbar and from room temperature to a few hundred degrees celsius. Our investigation shows that under CO exposure, above a certain temperature, carbon dissolves into the Pd particles forming a carbide phase. Upon exposure to CO and O(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
40
2
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 39 publications
10
40
2
4
Order By: Relevance
“…They provide clear indications of considerable C bulk concentrations within Pd, but only in the presence of CH 4 gas. The C 1s component at a BE of 283.0 eV (upper panel, green), as well as the Pd 3d component at 335.6 eV (lower panel, green) correspond well to literature‐reported values of 335.6 eV and 282.9 eV for Pd modified by bulk‐dissolved carbidic/interstitial C22, 26 and are obviously linked to ongoing C supply via the gas phase. The bulk character of this species is supported by its response to a change of the photon energy/C 1s kinetic energy, as shown in the Supporting Information, Figure S5.…”
supporting
confidence: 82%
“…They provide clear indications of considerable C bulk concentrations within Pd, but only in the presence of CH 4 gas. The C 1s component at a BE of 283.0 eV (upper panel, green), as well as the Pd 3d component at 335.6 eV (lower panel, green) correspond well to literature‐reported values of 335.6 eV and 282.9 eV for Pd modified by bulk‐dissolved carbidic/interstitial C22, 26 and are obviously linked to ongoing C supply via the gas phase. The bulk character of this species is supported by its response to a change of the photon energy/C 1s kinetic energy, as shown in the Supporting Information, Figure S5.…”
supporting
confidence: 82%
“…9 (lower part), most of the Pd3d signal resembles oxidic palladium (337.4 eV, FWHM = 1.99), with additional content of metallic Pd at 335.7 eV (FWHM = 1.38; Pd3d 5/2 ). The binding energy values are slightly higher compared to literature values because of the particle size effect that leads to an up-shift due to the small Pd particles in our case [18,[40][41][42]. Peak fitting showed that the oxidic content was 66%.…”
Section: Xps Investigation Before and After Co Oxidationcontrasting
confidence: 49%
“…However, in the case of the dispersion obtained in alcohol, the position of the Pd3d 5/2 line with E b = 335.5 eV rather exceeds the value typical of the compact metal. The formation of PdC x solid solutions is also possible because, according to the literature data, the typical E b value of surface palladium carbides is within the interval of ~335.6-336.0 eV [74][75][76][77][78] . This size effect shifts the photoelectron line towards higher binding energies [71][72][73] .…”
Section: Xps Studymentioning
confidence: 99%